Qualitative assessment of SARS‐CoV‐2‐specific antibody avidity by lateral flow immunochromatographic IgG/IgM antibody assay. Issue 2 (2nd August 2020) - Valdivia, Arantxa; Torres, Ignacio; Huntley, Dixie; Alcaraz, María J.; Albert, Eliseo; Colomina, Javier; Ferrer, Josep; Carratalá, Arturo; Navarro, David
Abstract: Knowledge of the precise timing of SARS‐CoV‐2 infection may be of clinical and epidemiological relevance. The presence of low‐avidity IgGs has conventionally been considered an indicator of recent infection. Here, we carried out qualitative assessment of SARS‐CoV‐2‐specific antibody avidity using an urea (6M) dissociation test performed on a lateral flow immunochromatographic IgG/IgM device. We included a total of 76 serum specimens collected from 57 COVID‐19 patients, of which 39 tested positive for both IgG and IgM and 37 only for IgG. Sera losing IgG reactivity after urea treatment (n = 28) were drawn significantly earlier ( P = .04) after onset of symptoms than those which preserved it (n = 48). This assay may be helpful to estimate the time of acquisition of infection in patients with mild to severe COVID‐19. Highlights: A LFIC test was adapted for assessing SARS‐CoV‐2 antibody avidity. This urea dissociation LFIC assay may hep to determine the time of SARS‐CoV‐2 infection.